2015
DOI: 10.1038/nclimate2824
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic analysis of IPCC summaries for policymakers and associated coverage

Abstract: but not policy-prescriptive 6 . We would therefore expect SPMs to reflect these principles by adopting a clear and neutral language that can be understood by a non-specialist audience.At the same time, it is of crucial importance how the print media interpret the results presented by the IPCC, as pivotal agents in science communication 7 to the general public.Previous research has focused on the way in which IPCC probabilistic statements are interpreted 8,9 , and on the discursive construction of the IPCC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 30 publications
0
64
0
3
Order By: Relevance
“…While this was accepted as a result of the nature of the evidence assessed and reference in the reports, and generally it was felt that there had been a noticeable improvement in the language in the IPCC ARs over the years, this is perceived as a significant shortcoming when engaging with audiences such as local policymakers, local businesses, councils, schools, community groups, stakeholders, members of the public, and internal staff. Such observations by users also chime with some of the academic research described in the section "The IPCC and decisionmaking" above (Black (2015), Barkemeyer et al (2015) and Dessai et al (2009). The plea for clearer, more accessible language has been echoed by other key users of the IPCC reports and their target audiences, such as business sectors, NGOs, and the media (Painter, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this was accepted as a result of the nature of the evidence assessed and reference in the reports, and generally it was felt that there had been a noticeable improvement in the language in the IPCC ARs over the years, this is perceived as a significant shortcoming when engaging with audiences such as local policymakers, local businesses, councils, schools, community groups, stakeholders, members of the public, and internal staff. Such observations by users also chime with some of the academic research described in the section "The IPCC and decisionmaking" above (Black (2015), Barkemeyer et al (2015) and Dessai et al (2009). The plea for clearer, more accessible language has been echoed by other key users of the IPCC reports and their target audiences, such as business sectors, NGOs, and the media (Painter, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, localized expertise, in the form of indigenous knowledge features scarcely in the IPCC reports (particularly WGII) challenging the extent to which the knowledge base assessed in the ARs is sufficiently inclusive of expertise and understanding of vulnerability, expertise, experiences and characterization of impacts and adaptation associated with climate change (Ford et al, 2012). As targets implemented through international and national policies will affect and require participation by ordinary citizens, their awareness, understanding, engagement and personal action is necessary to ensure uptake of measures and sustained changes to fill gaps where legislation and technology are insufficient to achieve success on their own (Barkemeyer et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk assessments are a common way to structure decision making processes in business, government and project work. A risk framing here calls for assessing and managing risks even if the specifics of climate change impacts are not, or cannot be, quantified; it calls for action also in the face of uncertainty (Barkemayer et al 2015;Moser and Dilling 2011;van der Linden et al 2015).…”
Section: Riskmentioning
confidence: 99%
“…A 2005 study on climate change in the media revealed that articles often frame climate change as a debate, controversy, or uncertainty, which is inconsistent with how the phenomenon is framed within the scientific community [2]. A recent 2015 linguistic study determined that the IPCC summaries, intended for non-scientific audiences, are becoming increasingly more complex and more difficult for people to understand [5], which highlights the critical interpretive role of the media in public discourse.…”
Section: Introductionmentioning
confidence: 99%